CHRONIC PAIN SYNDROME IN COMBAT VETERANS: BIOPSYCHOSOCIAL APPROACH TO PHYSICAL THERAPY AND INTERDISCIPLINARY REHABILITATION PROGRAMS - Степанова, Галина; Данько, Руслан; Кононенко, Андрій; Євтушенко, Олег; Рева, Любомир (SWorldJournal, 2025)
Introduction. Chronic pain syndrome is one of the most prevalent health problems among combat veterans, affecting approximately 30-40% of this population. The article provides a comprehensive analysis of modern approaches to physical therapy for chronic p